KINERJA PELAYANAN BERKAS KEPEGAWAIAN DI KANTOR REGIONAL I BKN YOGYAKARTA - , MUHAMMAD FAHRURROZI; , Dr. Bevaola Kusumasari, MPA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Development of regional autonomy became an endless issue, because the changes are systemically impact on the change in the service system in public organization. Kanreg I BKN Yogyakarta is one of the implementor and the pilot project of bureaucracy reform, therefore Kanreg I BKN performance in service can be measured by government organizations towards good governance . This research is a descriptive study with a qualitative analysis which aimed to obtain a description of public services performance, with a focus on research to determine the performance of the civil servant documents at the Kantor Regional I Badan Kepegawaian Negara Yogyakarta which had been seen from the service indicator based on the excellent service parameters of Kemenpan No. 63/2003 . This study used data collection methods such as observation , interviews and study related documents . The data were obtained and analyzed qualitatively to obtain a description of the processes and overall service performance BKN and what factors that affect the performance of such services. Based on the results of this study, the researcher concluded that the process of civil servant documents at Kanreg I BKN has been good. This process of civil servant documen in accordance with the system and procedures. But there are some things to consider , among others